OIL EXTRACTION AND RESOURCE SCARCITY: AN IN-DEPTH ANALYSIS OF US TRENDS - Sharif, Zaremba (International Journal of Allied Research in Economics (IJARE), 2023)
Natural resource scarcity is a multifaceted concern that has evolved over time, encompassing shifts in the cost, quality, and availability of energy and materials, as well as the growing shortage of ecosystem services crucial for human economic survival. This paper investigates the intricacies of natural resource scarcity by focusing on oil resource extraction in the United States, examining both economic and biophysical indicators. The economic indicators under scrutiny comprise the market prices of crude oil and natural gas, the unit cost of extraction, and the average total extraction cost. Additionally, the study explores the energy return on investment (EROI) as a pivotal biophysical indicator. The extraction of oil resources has undergone a noteworthy transformation, transitioning from a period of decreasing scarcity to one of increasing scarcity, notably around the 1960s. This transition raises a pertinent question: can economic growth be sustained within the constraints of a finite natural world? This study delves into these economic and biophysical indicators, aiming to provide a comprehensive view of natural resource scarcity and its implications. It considers the evolving nature of scarcity and the strategies adopted to address these scarcities, and how they have shaped economic growth. With an increasing global population and greater resource utilization, it is essential to comprehend how humans have responded to signals of heightened resource scarcity.